Permanent health education: Development of an informative guide with nutritional guidelines for professionals in Primary Health Care (Research, Society and Development, 2022)
Introduction: Permanent Education in Health, instituted and strengthened by the Brazil’s Ministry of Health, is an important instrument to develop professional improvement and qualification, and the Family Health Strategy is one of the most appropriate spaces for its realization. The nutritionist in primary care is a generator of knowledge and can develop such activities and increase the ability to resolve the demands of the teams. The present work aimed to develop an informative mini-guide that can help professionals from the Family Health Strategy teams in the nutritional guidelines of users served. Method: Descriptive study with a qualitative approach, based on the Problematization Methodology, with application of the Arch of Maguerez, carried out in a Primary Care Services Management in the Federal District, Brazil. Results and Discussion: During the observation, the structure, functioning and work process in the Basic Health Units linked to this management were verified, highlighting the high demand for sharing cases with Nasf-AB, including for nutrition. After defining the key points and theorizing, it was decided to implement actions of Permanent Education in Health, as a hypothesis of a solution, with the development of a mini-guide with updated nutritional guidelines for health professionals and a folder for users. Conclusion: The elaboration of teaching materials for Permanent Education in Health is an important action tool for the most diverse needs in the health care of the population, since it has easy dissemination and low investment.